Soft–Rigid Heterostructures with Functional Cation Vacancies for Fast‐Charging and High‐Capacity Sodium Storage - Su, Yu; Johannessen, Bernt; Zhang, Shilin; Chen, Ziru; Gu, Qinfen; Li, Guanjie; Yan, Hong; Li, Jia‐Yang; Hu, Hai‐Yan; Zhu, Yan‐Fang; Xu, Sailong; Liu, Huakun; et al. (Advanced materials (Weinheim), 2023)
Optimizing charge transfer and alleviating volume expansion in electrode materials are critical to maximize electrochemical performance for energy‐storage systems. Herein, an atomically thin soft–rigid Co9S8@MoS2 core–shell heterostructure with dual cation vacancies at the atomic interface is constructed as a promising anode for high‐performance sodium‐ion batteries. The dual cation vacancies involving VCo and VMo in the heterostructure and the soft MoS2 shell afford ionic pathways for rapid charge transfer, as well as the rigid Co9S8 core acting as the dominant active component and resisting structural deformation during charge–discharge. Electrochemical testing and theoretical calculations demonstrate both excellent Na+‐transfer kinetics and pseudocapacitive behavior. Consequently, the soft–rigid heterostructure delivers extraordinary sodium‐storage performance (389.7 mA h g−1 after 500 cycles at 5.0 A g−1), superior to those of the single‐phase counterparts: the assembled Na3V2(PO4)3||d‐Co9S8@MoS2/S‐Gr full cell achieves an energy density of 235.5 Wh kg−1 at 0.5 C. This finding opens up a unique strategy of soft–rigid heterostructure and broadens the horizons of material design in energy storage and conversion. The concept of a soft–rigid Co9S8@MoS2 heterostructure is proposed and realized in sodium‐ion batteries, which is confirmed by electrochemical tests and theoretical calculations. The synergy of heterostructure and functional cation vacancies can effectively lower the mechanical stress, decrease Na+‐diffusion barriers and maintain structural stability, resulting in high rate capacity and remarkable cycling performance.